Who decides? The sentence of the Supreme Court of the United States ruled in case 595 US (2022) National Federation of Independent Business and Ohio versus OSHA - Íñiguez Manso, Andrea (Derecho Público Iberoamericano, 2022)
This article has the purpose to analize the sentence of the United States Supreme Court in case 595 US (2022), that overturned the vaccine mandate issued by the OSHA. There are two areas that are important in this sentence for the judiciary doctrine. In the first place, the doctrine of non delegation and separation of power and in second place, the relationship between the law that creates an agency and the executive decrees dictated by those same agencies.